2012
DOI: 10.1089/aid.2011.0053
|View full text |Cite
|
Sign up to set email alerts
|

How Can HIV-Type-1-Env Immunogenicity Be Improved to Facilitate Antibody-Based Vaccine Development?

Abstract: No vaccine candidate has induced antibodies (Abs) that efficiently neutralize multiple primary isolates of HIV-1. Preexisting high titers of neutralizing antibodies (NAbs) are essential, because the virus establishes infection before anamnestic responses could take effect. HIV-1 infection elicits Abs against Env, Gag, and other viral proteins, but of these only a subset of the anti-Env Abs can neutralize the virus. Whereas the corresponding proteins from other viruses form the basis of successful vaccines, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 162 publications
(202 reference statements)
1
77
0
Order By: Relevance
“…It has been reported that increased CD40 stimulation, either by an anti-CD40 Ab or by transgenic CD40L overexpression, augments early Ab responses but significantly reduces their t 1/2 due to premature germinal center regression (54,55). In line with these observations is the remarkably short lifespan of Env-specific Abs induced by vaccination (56)(57)(58).…”
Section: Discussionmentioning
confidence: 75%
“…It has been reported that increased CD40 stimulation, either by an anti-CD40 Ab or by transgenic CD40L overexpression, augments early Ab responses but significantly reduces their t 1/2 due to premature germinal center regression (54,55). In line with these observations is the remarkably short lifespan of Env-specific Abs induced by vaccination (56)(57)(58).…”
Section: Discussionmentioning
confidence: 75%
“…However, the improvement in immunogenicity is not yet good enough to conclude that any forms of gp140 trimers, in their current iteration, are good enough to use in practical HIV-1 vaccines. The challenge is to determine what structural and other factors limit the immunogenicity of gp140 trimers and design ways to overcome any problems that are identified (22). Structural studies are of critical importance in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, this realization introduces another major challenge: Antibody responses to gp120-based vaccines persist poorly in humans or other mammalian species (reviewed in ref. 22). The point is moot whether this problem is unique to HIV gp120 or extends to responses against other viral vaccines, as suggested for the influenza virus hemagglutinin (23); it must be solved for an effective HIV vaccine.…”
mentioning
confidence: 99%